Prevalence of mental distress and associated factors among medical students of University of Gondar, Northwest Ethiopia: a cross-sectional study - Gidey Rtbey; Shegaye Shumet; Belete Birhan; Endalamaw Salelew (BMC Psychiatry, 2022)
Abstract Background Mental distress is the most common problem among medical students. This is associated with severe consequences of lack of empathy for their patients, committing medical errors, and suicidal ideations and attempts. However, there is limited data on this aspect where the study was conducted especially in this segment of the population. Considering its seriousness, this study will have pivotal input information to plan possible interventions for the future. So, this study is aimed at assessing the prevalence of mental distress and its associated factors among medical students of the University of Gondar, Northwest Ethiopia, 2021. Methods An institutional-based cross-sectional study was conducted using a stratified random sampling technique to get a total of 438 study subjects from April 15–30/2021. Mental distress data were collected using a self-administrated questionnaire of the 10-item Kessler Psychological Distress Scale. Data was entered to Epi-data version 4.6.02 and cleaned, coded, and analyzed using STATA version 14. Results The prevalence of mental distress among medical students was 193(45.95%) with 95% CI (41.2, 50.7). In multi-variable logistic regression being female sex (AOR = 4.5, 95% CI = 2.66, 8.12), lack of interest towards field of study (AOR = 4.4, 95%, CI = (2.18, 8.78), current alcohol use (AOR = 5.8, 95% CI = 3.03, 11.15), monthly pocket money < 735 Ethiopian birr (AOR = 3.1, 95% CI = 1.53, 6.04), extremely high test anxiety (AOR = 3.9, 95% CI = 1.27, 11.88), family history mental illness (AOR = 2.5 95% CI = 1.12, 5.53) and poor social support (AOR = 4.2, 95% CI = (1.94, 9.16) were significantly associated with mental distress. Conclusion and recommendation Prevalence of mental distress among medical students of University of Gondar was found to be higher when compared to previous studies among this population in Ethiopia. It is recommended that the school of medicine should give undue attention to address those identified factors by establishing counseling centers to minimize mental distress.